Medicinal and food plant: Cistanches Herba, a potential therapeutic hope for Parkinson's disease and related complications - Guoxue Zhu; Chengcheng Xu; Shujun Jiang; Zhennian Zhang; Wang Wang (Journal of Agriculture and Food Research)
Parkinson's disease (PD), the second most common neurodegenerative disorder, currently lacks disease-modifying treatments. The conventional therapeutic approach, which focuses on targeting individual molecules, falls short in addressing the complex pathology of PD. Cistanches Herba, a medicinal herb also recognized as a functional food, has shown therapeutic potential in mitigating PD and its associated complications through various mechanisms. In this review, we conducted thorough searches across PubMed and Web of Science using a range of keywords such as ''Parkinson's disease,'' ''Cistanches Herba,'' ''Medicine Food Homology,'' ''chemical component,'' ''prescriptions,'' ''complications,'' ''mechanism,'' ''safety,'' and ''toxicity,'' as well as different keyword combinations. Our findings indicate that Cistanches Herba, along with its active compounds and formulations, exerts therapeutic effects in PD through neuroprotection, anti-inflammatory activity, and other mechanisms. This multi-component, multi-target strategy underscores the herb's broad therapeutic potential. Additionally, we critically assess the safety and toxicity profile of Cistanches Herba, laying the groundwork for its safe and effective clinical application. This review offers a comprehensive overview of the pharmacological properties of Cistanches Herba in treating PD and its complications, providing new insights into its therapeutic potential and contributing to the expanding body of research on PD.